Post-processing techniques of additively manufactured Ti-6Al-4V alloy: A complete review on property enhancement - Singh P.K.; Kumar S.; Verma G.K.; Jain P.K. (My University, 2025)
Due to extensive research from academic institutions, companies, and research organizations around the world, Additive Manufacturing (AM) technology has reached its pinnacle in both research and commercial production. The AM processes help to produce a product from the CAD model by tessellation, as well as reduce the time it takes to build a product. Despite the fact that the AM processes have numerous benefits over the conventional manufacturing process, they still have several significant disadvantages, such as poor surface roughness and low mechanical properties. So, nearly all AM components require “post-processing” to attain the required mechanical properties, good surface finish, and dimensional accuracy. This post-processing include heat treatment, hot isostatic pressing (HIP), removal of the support structure, removal of the component from the build plate, surface finishing procedures, etc. In the AM processes, residual stress develops during processing, and it has been relieved by treatment in the heat before removing the parts from the build. The HIP process is used to make fully dense parts by consolidating the metals and providing microstructure homogeneity by removing the porosity, voids, and internal cracks. There are many methods of surface treatment, like bead blasting, machining, polishing, abrasive flow machining (used for internal surfaces), etc. In the shot peening treatment, compressive residual stress, micro-hardness, and corrosion resistance have been improved. Surface roughness is one of the main disadvantages of AM, so there are many methods used to improve the surface finish, like abrasive finishing, abrasive blasting, or bead blasting, etc. In this chapter, we discussed the different post-processing techniques used for enhancing the properties of additively manufactured Ti-6Al-4V alloy. © 2024 selection and editorial matter, Zafar Alam, Faiz Iqbal, and Dilshad Ahmad Khan.